2022
DOI: 10.3389/fimmu.2022.886698
|View full text |Cite
|
Sign up to set email alerts
|

Natural Exposure- and Vaccination-Induced Profiles of Ex Vivo Whole Blood Cytokine Responses to Coxiella burnetii

Abstract: Q fever is a zoonotic disease caused by the highly infectious Gram-negative coccobacillus, Coxiella burnetii (C. burnetii). The Q fever vaccine Q-VAX® is characterised by high reactogenicity, requiring individuals to be pre-screened for prior exposure before vaccination. To date it remains unclear whether vaccine side effects in pre-exposed individuals are associated with pre-existing adaptive immune responses to C. burnetii or are also a function of innate responses to Q-VAX®. In the current study, we measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“…Overall, of the bulk cytokine responses evaluated, IFNγ and IL-2 were the most informative for inferring prior exposure. Innate cytokines TNFα and IL-1β also showed some association with prior exposure by natural infection, consistent with previous results ( 43 ), but elevation was more marginal and restricted to specific subgroups of pre-exposed individuals.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Overall, of the bulk cytokine responses evaluated, IFNγ and IL-2 were the most informative for inferring prior exposure. Innate cytokines TNFα and IL-1β also showed some association with prior exposure by natural infection, consistent with previous results ( 43 ), but elevation was more marginal and restricted to specific subgroups of pre-exposed individuals.…”
Section: Resultssupporting
confidence: 91%
“…In our study, using CyTOF we also identified a population of C. burnetii -specific CD4 T cells (CD137 + CD154 + CD69 + IFNγ + IL-2 + TNFα + ) that was significantly increased in IGRA-positive individuals, particularly those who had exhibited clinical symptoms and remained seropositive. Co-production of these cytokines by specific cell subsets is consistent with data from a prior study looking at bulk cytokine responses to C. burnetii in individuals with prior exposure to C. burnetii ( 43 ), which showed that individuals with prior exposure and high IFNγ production also produce high amounts of IL-2. Notably, the CD137 + CD154 + CD69 + IFNγ + IL2 + TNFα + CD4 T cell cluster C11 and the corresponding lineage-negative innate cell cluster C19 were the only two cell populations showing clear IFNγ production based on the expression-normalized CyTOF data used for unsupervised clustering.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Increased levels of IL10 , TNFα and IL1β were previously described in peripheral blood of infected pregnant goats before or after parturition 9 . IL1β, IL6 and TNFα production were higher in naturally infected individuals compared to vaccinated ones 46 . Increased levels of inflammatory cytokines (i.e.…”
Section: Discussionmentioning
confidence: 80%